Penerapan Teknik Relaksasi Napas Dalam Pada Pasien Pasca Apendektomi Dengan Masalah Nyeri Akut - Susanti, Eva; Sulistini, Rumentalia; Anggraini, Fadilla (JKM : Jurnal Keperawatan Merdeka, 2024)
Background: Appendectomy is an operation performed to cut the inflamed appendix. The complaint that often arises after appendectomy surgery is acute pain. The aim is to get an overview of the implementation of deep breathing relaxation nursing to overcome the problem of acute pain in post-appendectomy patients at the Muhammadiyah Palembang Hospital. The case study subjects that will be studied are two people, a man and a woman after appendectomy with acute pain problems. Method: using analytical descriptive methods in the form of case studies to provide comprehensive nursing care. Results After implementing the nursing relaxation technique of deep breathing 3 times a day for 2 minutes on 3 consecutive days, the two post-appendectomy patients experienced a decrease in the pain scale. In patient 1, from a pain scale of 5 down to a pain scale of 2 and in patient 2, from a pain scale of 6 down to a pain scale of 2. Conclusion: The application of deep breathing relaxation techniques to both post-appendectomy patients can reduce the intensity of pain from a moderate pain scale to a mild pain scale.